Pendidikan Nilai Kejujuran Berbasis Kesadaran Ilahiah dalam Kitab Akhlāq Lil Banīn (Kajian Pasal al-Walad al-Amīn) - Krisna Wijaya; Djamaluddin Perawironegoro; Abdul Hopid (Istifkar: Media Transformasi Pendidikan, 2026)
Character education, particularly the value of honesty, is a crucial issue in shaping children’s moral development in contemporary times. Honesty is not merely adherence to social rules but also a manifestation of divine awareness guiding consistent moral behavior. This study aims to analyze the teaching of honesty based on divine awareness in Kitab Akhlāq Lil Banīn, focusing on the chapter al-Walad al-Amīn. A qualitative library research approach was employed, including analysis of the primary text and secondary literature on Islamic character and moral education. The findings indicate that honesty is cultivated through an integrative pedagogical mechanism: rational dialogue, behavioral exemplars, persuasive advice, and internalization of moral consequences. Honesty is tested in the absence of external supervision, teaching children to regulate behavior through awareness of Allah’s oversight (muraqabah). This approach emphasizes internalization of moral values, rather than formal compliance. Divine awareness serves as the foundation for sustained honesty, fostering moral and spiritual integrity. This study contributes academically to understanding honesty education based on spiritual consciousness and offers a pedagogical model relevant to contemporary Islamic character education.